Pengaruh Solvabilitas dan Likuiditas terhadap Profitabilitas pada Perusahaan Tekstil dan Garmen yang Terdaftar di Bursa Efek Indonesia (BEI) - Az Zahra Putri Setyo Wati; Nazwa Abidin Yunus; Isti Pujihastuti (LPPM Politeknik Pratama, 2025)
This study aims to analyze the impact of Solvability (DER) and liquidity (CR) on profitability (ROA) in textile and garment companies listed on the Indonesia Stock Exchange (IDX) during the period of 2019–2023. The research is motivated by significant fluctuations in financial performance in the textile and garment sector due to global economic pressures, high debt burdens, and decreased demand post-COVID-19 pandemic. The research method used is a quantitative approach with purposive sampling technique on 10 companies as the research sample. The data used is secondary data in the form of annual financial statements. The analysis method employed in this study is multiple linear regression analysis. The results show that, partially, Solvability has a negative and significant impact on profitability, while liquidity has a positive and significant impact on profitability. Simultaneously, Solvability and liquidity have a significant impact on profitability. these finding contribute to the empirical on financial management and offer practical insights for textile and garment companies in formulating effective financial strategies to enchance profitability and long-term sustainability.